TEORI GELOMBANG DALAM BAHASA JAWA DIALEK BANYUMAS - Katrini, Yulia Esti (Majalah Transformatika, 2010)
Banyumas is one of the Javanese dialect which is used by the society lived in the west part of Central Java. It is different from standard Java language that mainly used in Solo and Yogyakarta. Dialectical differences can be explained by  wave  theory,  that  language development can spread in waves, so there are innovative and conservative areas. This means that the areas which are close with the center of culture and the one that become the center of linguistics will have more similarities of language variety than those ones farer. It concerns with the growth of Banyumas dialect used by the society is not affected by the development of Standard dialect of Javanese. Keywords : Banyumas dialect, standard Java language, and the wave theory.